2004
DOI: 10.1258/rsmmsl.44.2.127
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Homicidal Deaths in Delhi

Abstract: A meticulous post-mortem review was undertaken in the department of forensic medicine at the Maulana Azad Medical College (MAMC) to find out trends in homicides during the period 1992-1996. Standard procedures for autopsies and a review of the inquest papers were carried out. Out of 3,886 medico-legal autopsies performed in the department during the said period, only 232 cases (5.9%) were homicidal deaths. The commonest age group of the victims was 21-30 years (38%). Males were victimized three times more ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
24
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 3 publications
9
24
3
Order By: Relevance
“…The incidence of homicide in the present study was lower when compared to those observed by Murthy et al (6) 15.1%, Gupta et al (7) 7.5%, Sinha et al (8) 5.9%, Dhaval. (9) 9.13% and B.C.…”
Section: Discussioncontrasting
confidence: 75%
“…The incidence of homicide in the present study was lower when compared to those observed by Murthy et al (6) 15.1%, Gupta et al (7) 7.5%, Sinha et al (8) 5.9%, Dhaval. (9) 9.13% and B.C.…”
Section: Discussioncontrasting
confidence: 75%
“…In the forensic literature, several studies have already examined sharp force suicides and homicides [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, there are very few systematic comparative studies of hesitation marks and defense wounds [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Eftekhari et al suggested quarrel, burglary, and family conflicts as major reasons of committing murder in Tehran (1). Shah and Gupta, also, reported quarrel and robbery as main factors leading to murder in India (12,13). Considering these results, social workers could help prevent and decrease quarrel and aggression.…”
Section: Discussionmentioning
confidence: 98%